Cover Picture: Continuous Transfer Hydrogenation of Sugars to Alditols with Bioderived Donors over Cu–Ni–Al Catalysts (ChemCatChem 10/2015). Issue 10 (18th May 2015) - Scholz, David; Aellig, Christof; Mondelli, Cecilia; Pérez‐Ramírez, Javier
<x xml:space="preserve">Abstract</x> The front cover picture shows the give‐and‐take concept at the basis of a continuous transfer‐hydrogenation process for the reductive upgrading of renewable substrates. In their Full Paper Pérez‐Ramírez and co‐workers describe how the accurate selection of the catalyst precursor and metal ratio is key to generate a CuNiAl catalyst for the efficient and stable conversion of hexoses and pentoses to alditols. This heterogeneous catalyst is also able to transform suitable dehydrogenated alcohols by lactonization, thus obtaining additional relevant chemical intermediates in the same process. This system stands as a sustainable technology for the valorization of saccharide feedstocks in future biorefineries. More information can be found in the Full paper by Pérez‐Ramírez and co‐workers. The article highlighted by this cover can be found on p. 1551 ff. of Issue 10, 2015.